BJS-01 SARCOPENIA AND VISCERAL FAT IN PATIENTS WITH INCISIONAL HERNIA AFTER URGENT LAPAROTOMY. (13th October 2022) - Romano, L; Fiasca, F; Mattei, A; Tersigni, L; Gianneramo, C; Schietroma, M; Carlei, F; Giuliani, A
Abstract: Aim: Various risk factors have been associated with the development of incisional hernia (IH). Some recent papers underlined that visceral fat could be a reliable indicator. Another risk factor which is of increasing clinical interest is sarcopenia. Recent studies have identified it as an independent predictor of poor postoperative outcomes following abdominal surgery. We aimed to investigate the role of visceral fat and skeletal muscle as emerging risk factors for IH after urgent laparotomy. Material & methods: Patients aged 18 years or older who underwent urgent median laparotomy and with continuous direct suturing of the laparotomy were included. They were categorized into two groups: those with a median IH and those without IH at 12-months follow-up. Demographic data were prospectively collected while CT scans were retrospectively reviewed. The data were compared among two groups. Results: From January 2018 to May 2021, 364 patients underwent urgent surgery in our Department, of whom 222 were aged >18 years-old and underwent median laparotomy. Forty-four patients had diagnosis of median IH, while 41 patients without IH were identified as the control group. Statistically significant differences emerged for BMI and for the area of visceral fat. The association with the presence/absence of sarcopenia was not significant. Conclusions: When surgery is performed in urgent settings it could be important to identify patients at risk, especially as CT scans are generally available for all patients with urgent abdominal disease. In these patients a prophylactic mesh placement could be evaluated.